1.
\(y'=\left(2m+3\right)cosx+2-m\ge0;\forall x\)
\(\Leftrightarrow\left(2m+3\right)cosx\ge m-2\)
- Với \(m=-\frac{3}{2}\) thỏa mãn
- Với \(m>-\frac{3}{2}\Rightarrow cosx\ge\frac{m-2}{2m+3}\)
\(\Rightarrow\frac{m-2}{2m+3}\le\min\limits_Rcosx=-1\) \(\Leftrightarrow3m\le-1\Rightarrow m\le-\frac{1}{3}\Rightarrow-\frac{3}{2}< m\le-\frac{1}{3}\)
- Với \(m< -\frac{3}{2}\Rightarrow cosx\le\frac{m-2}{2m+3}\Rightarrow\frac{m-2}{2m+3}\ge\max\limits_Rcosx=1\)
\(\Leftrightarrow m-2\le2m+3\Rightarrow m\ge-5\)
Kết hợp lai ta được \(-5\le m\le-\frac{1}{3}\)
2.
\(y'=1+\left(m+1\right)cosx\le0;\forall x\in R\)
\(\Leftrightarrow\left(m+1\right)cosx\le-1\) ; \(\forall x\in R\)
- Với \(m=-1\) không thỏa mãn
- Với \(m>-1\Leftrightarrow cosx\le-\frac{1}{m+1}\)
\(\Rightarrow-\frac{1}{m+1}\ge1\Leftrightarrow m+1\le-1\Rightarrow m\le-2\) (ktm)
- Với \(m< -1\Leftrightarrow cosx\ge-\frac{1}{m+1}\Rightarrow-\frac{1}{m+1}\le-1\)
\(\Leftrightarrow m+1\ge1\Rightarrow m\ge0\) (ktm)
Vậy không tồn tại m để hàm đồng biến trên TXĐ